2008
DOI: 10.1002/hep.22112
|View full text |Cite
|
Sign up to set email alerts
|

Optical analysis of computed tomography images of the liver predicts fibrosis stage and distribution in chronic hepatitis C

Abstract: This study was undertaken to evaluate an image processing method for assessing liver fibrosis in conventional computed tomography (CT) scans in patients with chronic hepatitis C. Two cohorts (designated "estimation," n ‫؍‬ 34; and "validation," n ‫؍‬ 107) of chronic hepatitis C patients were assessed using digitized conventional helical CT. Weighted CT mean fibrosis (Fibro-CT) was calculated as a nonlinear weighted mean F-score for each sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 34 publications
0
37
0
1
Order By: Relevance
“…The theoretical advantages of these methods include the ability to analyze almost the entire liver and the applicability to patients with obesity or ascites. Preliminary studies in human subjects have confirmed the feasibility of these techniques for quantitative assessment of hepatic fibrosis [115][116][117][118][119]. In addition, a recent prospective comparative study in 96 patients with chronic liver disease [120] has suggested that MR elastography had a better diagnostic accuracy than TE for the diagnosis of significant fibrosis (AUROC: 0.99 vs. 0.84, respectively P \ 0.05).…”
Section: Novel Imaging Techniquesmentioning
confidence: 88%
“…The theoretical advantages of these methods include the ability to analyze almost the entire liver and the applicability to patients with obesity or ascites. Preliminary studies in human subjects have confirmed the feasibility of these techniques for quantitative assessment of hepatic fibrosis [115][116][117][118][119]. In addition, a recent prospective comparative study in 96 patients with chronic liver disease [120] has suggested that MR elastography had a better diagnostic accuracy than TE for the diagnosis of significant fibrosis (AUROC: 0.99 vs. 0.84, respectively P \ 0.05).…”
Section: Novel Imaging Techniquesmentioning
confidence: 88%
“…[18][19][20][21][22]27 Recently, it has been shown that CT or magnetic resonance (MR) perfusion imaging can detect microcirculatory changes caused by collagen deposits in the liver and pancreas. [18][19][20]22,28,29 Romero-Gomez et al 28 studied liver fibrosis in patients with chronic hepatitis C and concluded that optical digital analysis of conventional CT images is effective in determining the stage and distribution of liver fibrosis. Ronot et al 29 examined 52 patients with chronic hepatitis C who underwent perfusion CT and liver biopsy at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the results of this trial and results of multiple case reports of Caseiro regarding the SVR may be multifactorial: firstly, all Caseiro's patients were nonresponsive to previous conventional IFN/RBV therapy and retreated with Peg-IFN-α/RBV. Data from the clinical trials of retreatment with Peg-IFN-α/RBV in patients who were nonresponsive to previous IFN-α/RBV, referred to that SVR rates ranged from 8 to 35% (48)(49)(50)and these rates were generally higher than the reported rates (6 to 8%) (28,32) in prior non-responders to Peg-IFN-α/RBV retreated by the same regimen for 48 weeks as in our trial. So, we can't exclude that the difference is related to difference in modality of treatment.…”
Section: Discussionmentioning
confidence: 45%